Simulation of Improved Fourth-Order Colpitts Oscillator - Qiao, Xiaohua; Sun, Yuxia; Zhang, Hongqin; Xu, Yaping (International Journal of Online and Biomedical Engineering (iJOE), 2013)
A RLC parallel resonance circuit was built on the basis of the original fourth-order Colpitts oscillator. An improved Colpitts oscillator was given. The Lyapunov exponent spectrum, bifurcation diagram and phase trajectories of chaotic attractors were calculated by control theory and numerical methods. Analysis shows that the change of resistance value R of the RLC parallel resonance circuit to control Colpitts oscillator can obtain better dynamic characteristics than the original fourth-order Colpitts oscillator, and the control circuit implementation is very simple. More interestingly, it is found that the bifurcation behavior of the new system has the Fengenbaum first constant in the logarithm law. The experimental circuit of the new system was designed. The experimental results and theoretical analysis have a good consistency, indicating that this control scheme is of feasibility and better practicability.